Managing Strategic Buyers: the effect of commitment in the resale option - Beccuti, Juan (2017)
We study the seller’s pricing strategy of one good (finite inventory) that can be sold in two bargaining periods (before a deadline) when she faces two strategic buyers with private valuations. In particular, we are interested in analyzing the effect of allowing a resale option between buyers when the seller has commitment to future prices. First, allowing the resale option may decrease the whole sequence of prices. This price reduction is justified in the high impact of the resale option on early demand elasticity; that is, early purchases are highly responsive to prices. Second, when the seller can commit to prices, setting higher future prices increases the sensitivity of early purchases to changes in current prices. This effect is not credible without commitment, where buyers anticipate the incentives to reduce prices in the future. Thus, the commitment to set prices in advance generates an extra increase in seller’s profits when the resale option is allowed. Alternatively, we claim that there is a complementarity between commitment in the pricing policy and the resale option, improving the price discrimination strategy of the seller.